Implementation Of Home Children Learning Center Program The West Java Human Initiative On Children's Self-Concept In The City Of Bandung - Khansa Anisah; Ali Anwar Yusuf; Willya Achmad (Jurnal EduHealth, 2023)
The purpose of this research is to find out how the implementation of the HOME Children Learning Center program owned by the HSO West Java Human Initiative can affect a child's self-concept. This study uses a qualitative research approach using descriptive methods. Data collection techniques used are in-depth interviews, observation, and documentation studies. The results of this study are how to implement the HOME Children Learning Center program in the West Java Human Initiative and know self-concept and factors that influence children's self-concept based on the implementation of the Uman Initiative West Java HOME Children Learning Center program.